2020
DOI: 10.1158/0008-5472.can-20-1192
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Induces Resistance to EGFR Inhibitors in Lung Cancer Cells via Upregulation of FGFR1 and the MAPK Pathway

Abstract: ◥Development of resistance remains the key obstacle to the clinical efficacy of EGFR tyrosine kinase inhibitors (TKI). Hypoxia is a key microenvironmental stress in solid tumors associated with acquired resistance to conventional therapy. Consistent with our previous studies, we show here that long-term, moderate hypoxia promotes resistance to the EGFR TKI osimertinib (AZD9291) in the nonsmall cell lung cancer (NSCLC) cell line H1975, which harbors two EGFR mutations including T790M. Hypoxia-induced resistance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 45 publications
4
45
0
Order By: Relevance
“… 20 A recent study shows that hypoxia-induced resistance to osimertinib is driven by overexpression of fibroblast growth factor receptor 1 (FGFR1) to sustain ERK signaling and subsequent attenuation of Bim induction, which can be overcome by combining with an FGFR1 or MEK inhibitor. 21 In agreement, other studies, albeit with different rationales, also demonstrate a critical role of functional Bim in mediating apoptosis induced by osimertinib, other third-generation EGFR-TKIs or the combination of osimertinib with other agents in EGFR-mutant NSCLC cells. 22–26 …”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“… 20 A recent study shows that hypoxia-induced resistance to osimertinib is driven by overexpression of fibroblast growth factor receptor 1 (FGFR1) to sustain ERK signaling and subsequent attenuation of Bim induction, which can be overcome by combining with an FGFR1 or MEK inhibitor. 21 In agreement, other studies, albeit with different rationales, also demonstrate a critical role of functional Bim in mediating apoptosis induced by osimertinib, other third-generation EGFR-TKIs or the combination of osimertinib with other agents in EGFR-mutant NSCLC cells. 22–26 …”
Section: Introductionsupporting
confidence: 70%
“… 40 Beyond the RAS-dependent resistance models, MEK inhibition with trametinib synergized with osimertinib to suppress the growth of EGFR-mutant NSCLCs expressing a B-Raf fusion 45 or resistant tumors with elevated expression of FGFR1 and activated MEK/ERK signaling. 21 …”
Section: Introductionmentioning
confidence: 99%
“…In another model, NSCLC cell lines with EGFR alterations (including T790M mutation, sensitizing to Osimertinib) were exposed to Osimertinib with a chronic and moderate hypoxic atmosphere. Interestingly, hypoxic NSCLC cell lines developed a resistance associated with a mesenchymal polarization and supported by FGFR1 (fibroblast growth factor receptor 1), largely resulting from mitogen-activated protein kinases (MAPK) pathway activation [ 129 ].…”
Section: Biological Features Associated With Hypoxia In Nsclcmentioning
confidence: 99%
“…In addition, one study has reported that microRNAs, metabolic pathways, and pseudohypoxia initiate drug tolerance to EGFR inhibitors in lung adenocarcinoma (47). Lu et al demonstrated that prolonged, long-term, moderate hypoxia can promote resistance to the third-generation EGFR-TKI osimertinib (AZD9291) in the NSCLC cell line H1975 that had developed resistance to firstand second-generation EGFR-TKIs via the T790M EGFR mutation (43,48). Hypoxia exposure induces gefitinib resistance in both EGFR-wild type and EGFRmutated NSCLC through epigenetic changes and regulation of epithelial-mesenchymal transition (EMT) (49)(50)(51).…”
Section: Hypoxia-induced Chemotherapy Resistance In Nsclcmentioning
confidence: 99%
“…Recent experiments using tumor cell lines also support that hypoxia-induced HIF-1α can increase PD-L1 expression on tumor cells, via direct interaction with a hypoxia-response element in the PD-L1 proximal promoter to activate transcription ( 42 ). Hypoxia may also be an important mediator of resistance to EGFR-TKIs via the upregulation of FGFR1 and the MAPK pathway in the NSCLC cell line H1975 ( 43 ).…”
Section: Hypoxia-induced Chemotherapy Resistance In Nsclcmentioning
confidence: 99%